Frequency-dependent OPFET characteristics with improved absorption under back illumination - Roy N.S.; Pal B.B. (My University, 2025)
A simple analytical model of an ion-implanted GaAs metal-semiconductor-field-effect transistor (MESFET) is useful for computer aided design of GaAs devices and integrated circuits (IC's) and device parameter acquisition. The present paper aims at presenting a frequency dependent analytical model of GaAs optically illuminated field-effect transistor (OPFET) with improved absorption under back illumination. Instead of the conventional front illumination through the source, gate and drain we consider the incident radiation to enter the device through the substrate. Two cases are considered: one in which the fiber is inserted partially into the substrate and the other, in which the fiber is inserted upto the active layer - substrate interface. The later case represents improved absorption in the active layer of the device. The current-voltage characteristics and the transconductance of the device for different signal modulated frequencies have been evaluated. The frequency dependence of internal and external photovoltages and the photocurrent have also been calculated and discussed. The results indicate significant improvement over published data using front illumination.